These are the tools of the present. Beirut, Cairo. - Abu ElDahab, Mai; Slater, Marnie (Brussels : Mophradat, 2017)
Abu Hamdan, Lawrence ; Aivazian, Haig ; Al Solh, Mounira ; Aly, Doa ; Andeel ; Helmy, Malak ; Arsanios, Mirene ; Issa, Iman ; Khaled, Mahmoud ; Louca, Maurice ; Metwaly, Jasmina ; Namy, Joe ; Nile Sunset Annex ; Samaha, Roy ; Sehnaoui, Sharif ; Stephan, Rania ; Wavelet, Christopher ; Wetmore, Lauren
Interviews, commissioned research by Mophradat, between February 2016 and February 2017
boek